Flavonoids from the cultured cells of Glycyrrhiza uralensis. Issue 3 (3rd March 2016) - Feng, Ke-Ping; Chen, Ri-Dao; Li, Jian-Hua; Tao, Xiao-Yu; Liu, Ji-Mei; Zhang, Min; Dai, Jun-Gui
Abstract : Two new flavonoids (1 and2 ), along with 14 known ones (3 –16 ), were isolated from the cultured cells of Glycyrrhiza uralensis . Most of them were prenylated flavonoids. Their structures were elucidated on the basis of spectroscopic data analysis. All compounds showed non-cytotoxicity against five human tumor cell lines. The results suggest that plant cultured cells can yield the secondary metabolites that have not been found in parent plant.